Development and Engineering Application of a Ground Harmonic Control Device - WU Xinhong; KONG Zhongqiu; HUANG Chao; ZHANG Zhixue; SHEN Hui (Kongzhi Yu Xinxi Jishu)
It proposes a method for harmonic control of AC traction network, using active filter devices and passive filter devices to filter out low-order and high-order harmonic currents separately in traction network. This method can also be used for reactive power compensation. Ground harmonic control device developed from this method has been tested and practically used. Results show that the device has good effects on harmonic and reactive power control, and can eliminate the risks of resonance between locomotive and network effectively.